An Analysis of Classroom Management Problems in Teaching English Speaking Skills at SMP Negeri 1 Gunungsitoli Idanoi - Septrida Gea; Afore Tahir Harefa; Hidayati Daeli; Kristof Martin Efori Telaumbanua (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to analyze classroom management problems in teaching English speaking skills at SMP Negeri 1 Gunungsitoli Idanoi in the 2024/2025 academic year. The research was conducted at SMP Negeri 1 Gunungsitoli Idanoi, Gunungsitoli City, North Sumatra, from July to August 2025. The population of this study consisted of eighth-grade students, with one English teacher and 20 students selected as research participants. This study employed a descriptive qualitative approach. Data were collected using observation checklists, semi-structured interviews, and documentation to obtain comprehensive information related to classroom management practices. The collected data were analyzed using qualitative data analysis techniques, including data condensation, data display, and conclusion drawing and verification. The results of the study revealed that classroom management in teaching English speaking skills had not been implemented optimally. Several classroom management indicators, such as effective time management, disciplinary control, the use of instructional media, and group or pair management, were not consistently applied during speaking activities. These conditions resulted in a noisy classroom atmosphere and uneven student participation. The main factors influencing these problems included students’ low motivation and interest, differences in language proficiency levels, limited school facilities, lack of teaching media, and teachers’ difficulties in managing time and maintaining classroom discipline. In conclusion, effective classroom management plays a crucial role in supporting the success of English speaking instruction. Therefore, English teachers are expected to improve classroom discipline, utilize technology-based learning media, and manage instructional time more efficiently to enhance students’ speaking performance.